PELAKSANAAN PENDEKATAN PERUBAHAN TINGKAH LAKU OLEH GURU SEJARAH DI SMA N 1 BASO - Rhamadani, Sri - (Pendidikan Sejarah, 2014)
The teacher is an important person in role of students learning styles, leading students to learn better and motivated students to learn. This study was partly motivated by the history teacher has not made changes in student behavior.Bade on the problem, this study is focused on the implementation of Behavioral change approach by history teacher in high school 1 Baso. This study aims to describe the implementation of behavior change approach by history teacher in high school 1 Baso. The study is a descriptive qualitative research with location in SMA N 1 Baso. The informants in this study include headmaster, history teachers and students by documentation technique in the form of lesson plans, observations and interviews. The accuracy of the data was tested by using triangulation of data, from data had collected analyzed with an interactive model that consists of data collection, data reduction, data presentation and conclusion. The results of the study showed that the implementation of behavior change approach by History Teacher in High School 1 Baso, using positive reinforcement has been done by the history teacherâs, the punishment carried out by one teacher, delayed punishment conducted by one teacher, and negative reinforcement is done by one the teacher. Although the history teacherâs know the benefits of the implementation of this approach is a change in behavior, but teachers are still not able to practice fully. Based on this study can be concluded that the history teacher Hihg school 1 Baso been implementing a change in behavior towards students, although not all are fully implemented approach.